2013
DOI: 10.1021/ol400363f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Rh-Catalyzed Domino Transformations of Alkynylcyclohexadienones with Organoboron Reagents

Abstract: A new enantioselective rhodium-catalyzed domino reaction is described that gives access to fused heterocycles by desymmetrization of alkyne-tethered cyclohexadienones. Two new C-C bonds and two stereocenters are formed in one step with good enantioselectivity. In contrast to prior reports, it was found that a vinylidene is not involved in the product formation but that syn-addition of the rhodium-aryl species onto the alkyne takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(38 citation statements)
references
References 38 publications
0
37
0
1
Order By: Relevance
“…The Sasai and Enders groups used a phosphinothiourea to enable a Rauhut–Currier reaction to form bicyclic enones [16]. The Tian and Lin group used alkyne-tethered cyclohexadienones in an arylrhodation/conjugate addition sequence that enantioselectively delivered oxabicyclo[4.3.0]nonanes [17]; the Lautens and Lan groups have also contributed to the further development of this reaction [1819]. The Rovis group employed cyclohexadienone hydroperoxides in a chiral phosphoric acid-catalyzed [1,2]/[1,4]-addition cascade [20].…”
Section: Resultsmentioning
confidence: 99%
“…The Sasai and Enders groups used a phosphinothiourea to enable a Rauhut–Currier reaction to form bicyclic enones [16]. The Tian and Lin group used alkyne-tethered cyclohexadienones in an arylrhodation/conjugate addition sequence that enantioselectively delivered oxabicyclo[4.3.0]nonanes [17]; the Lautens and Lan groups have also contributed to the further development of this reaction [1819]. The Rovis group employed cyclohexadienone hydroperoxides in a chiral phosphoric acid-catalyzed [1,2]/[1,4]-addition cascade [20].…”
Section: Resultsmentioning
confidence: 99%
“…26 Subjecting substrates 55 and aryl boronic acids to catalytic [Rh(coe) 2 Cl] 2 in the presence of chiral diene ligand 57 provided bicyclic enones 56 in moderate yields and with good stereocontrol (Scheme 12). The authors found that the stereoselectivity of the reaction was generally insensitive to both the nature of the aryl boronic acid and to variations of the alkyne tether (products 58 – 61 ).…”
Section: Transition Metal-catalyzed Desymmetrizationsmentioning
confidence: 99%
“…Thesubsequent treatment of 3aunder acidic conditions gave the desired cyclohexenone 4a with an all-carbon quaternary center at the g-position in 52 %y ield (Table 1, entry 1). Next, we examined the effect of the substituents on [Rh(Phebox-R)] (1;T able 1, entries [6][7][8]. Next, we screened aseries of hydrosilanes as reductants.Ofthe alkoxyhydrosilanes tested, the reaction with trimethoxysilane gave the best result (90 % yield, e.r.…”
mentioning
confidence: 99%